Prostate Intrafraction Translation Margins for Real-Time Monitoring and Correction Strategies - Dale W. Litzenberg; James M. Balter; Scott W. Hadley; Daniel A. Hamstra; Twyla R. Willoughby; Patrick A. Kupelian; Toufik Djemil; Arul Mahadevan; Shirish Jani; Geoffrey Weinstein; Timothy Solberg; Charles Enke; et al. (Prostate Cancer)
The purpose of this work is to determine appropriate radiation therapy beam margins to account for intrafraction prostate translations for use with real-time electromagnetic position monitoring and correction strategies. Motion was measured continuously in 35 patients over 1157 fractions at 5 institutions. This data was studied using van Herk's formula of (αΣ+γσ') for situations ranging from no electromagnetic guidance to automated real-time corrections. Without electromagnetic guidance, margins of over 10 mm are necessary to ensure 95% dosimetric coverage while automated electromagnetic guidance allows the margins necessary for intrafraction translations to be reduced to submillimeter levels. Factors such as prostate deformation and rotation, which are not included in this analysis, will become the dominant concerns as margins are reduced. Continuous electromagnetic monitoring and automated correction have the potential to reduce prostate margins to 2-3 mm, while ensuring that a higher percentage of patients (99% versus 90%) receive a greater percentage (99% versus 95%) of the prescription dose.